The extremely small body size of Williamson’s mouse deer (Tragulus williamsoni) allows coexistence with sympatric larger ungulates through temporal avoidance - He, Ru-Chuan; Wang, Lin; Goodale, Eben; Li, Kai; Quan, Rui-Chang (Frontiers in Ecology and Evolution, 2023)
Research on the coexistence of congeneric species is essential for understanding community assemblages. Smaller competitors are expected to avoid larger ones, either spatially or temporally, to reduce interspecific competition. According to the spatial scaling law, the greater the difference in body size, the weaker the competitive interactions of the competitors. However, this is not confirmed in the guild of tropical forest ungulates. In this study, we assessed the competitive interactions of Williamson's mouse deer (Tragulus williamsoni), one of the smallest ungulate species in the world, with sympatric larger ungulates and hypothesized that: 1) temporal avoidance plays a more important role than spatial avoidance for Williamson's mouse deer to alleviate extensive interspecific competition with larger ungulates due to its extremely small body size, and 2) the strength of avoidance increases with decreasing differences in body size. We set up 238 camera traps from January 2017 to January 2021 to survey Williamson's mouse deer and the sympatric larger ungulate species, that is, northern red muntjac (Muntiacus vaginalis), wild boar (Sus scrofa), Chinese serow (Capricornis milneedwardsii), and sambar (Rusa unicolor), in the protected areas of Mengla County, southwestern China. We then performed a spatio-temporal analyses, including occupancy models, daily activity patterns, and a time interval analysis. Spatially, there was no significant avoidance. Temporally, Williamson's mouse deer had different daily activity patterns and direct temporal avoidance of all larger ungulate species. The lack of spatial avoidance and strong temporal avoidance supported our first hypothesis, but the stronger avoidance of much larger species was against our second hypothesis. Our results revealed the coexistence mechanism between Williamson's mouse deer and sympatric larger ungulates and suggested that the difference in body size is limited in explaining the competitive interactions of tropical forest ungulates due to the effects of multiple 2 This is a provisional file, not the final typeset article ecological processes. This deepens our understanding of the relationship between species trait differences and community assembly in tropical forest ecosystems.